Clinical Profile of Patients of Pelvic Organ Prolapse and Its Associated Factors - Pudasaini, Sangita; Dangal, Ganesh (Journal of Nepal Health Research Council, 2023)
Background: Prolapse is among the most common indication for gynaecological surgery. It is difficult to estimate prevalence of pelvic organ prolapse even in developed countries due to lack of epidemiological studies. This study was done to find the prevalence, risk factors and common presenting complaints of women with pelvic organ prolapse.Methods: Women with pelvic organ prolapse visiting Paropakar Maternity and Women’s Hospital during 4 months duration in 2021 were approached and after obtaining an informed consent, all the patient information on various risk factors and clinical profile(age,parity,body mass index,smoking etc.) for pelvic organ prolpase were collected in a pre-developed proforma. Pelvic Organ Prolapse was classified by Pelvic Organ Prolapse Quantification system. Data analysis was done using statistical package for the social sciences-25. Ethical approval was taken from Institutional Review Committee- National Academy of Medical Sciences.Results: Out of 58 cases enrolled in the study, prevalence of pelvic organ prolapse was found to be 1.28%. Women belonging to age group ? 49 years was 91.4%. Bulge symptom was the most common presenting complain among the women, 98.3%. 50% of women (n=29) were grand multipara. 53.4% (n=31) of women had delivered their first baby before 20 years of age. Multiparity,vaginal birth and menopausal age were the common risk factors.Conclusions: Menopausal age, multi-parity, vaginal births, age at first vaginal delivery of less than 20 years were significant risk factors for development of prolapse. Bulge symptom was the most common presenting complaint. However,Smoking habit, overweight were not related to pelvic organ prolapse.Keywords: Pelvic organ prolapse; prevalence; risk factors